The effect of dietary supplementation of mucuna leaf meal on the growth performance, blood parameters, and carcass quality of broiler - Oloruntola, Olugbenga David; Ayodele, Simeon Olugbenga; Omoniyi, Idowu Samuel; Adeyeye, Samuel Adebowale; Adegbeye, Moyosore Joseph (Acta Scientiarum. Animal Sciences, 2022)
Three hundred 1-day old broiler chickens were used to assess the effects of Mucuna leaf meal (MLM) dietary supplementation on the performance, haemato-biochemical indices, oxidative status and meat of broiler chickens. Five experimental supplemented diets were formulated: diets: 1 (0% supplement), 2 (1.1 % OXYT), 3 (0.5% MLM), 4 (1.0 % MLM) and 5 (1.5% MLM). The final weight gain of the birds fed diets 2 and 5 was higher (p < 0.05) than those birds fed the control and other diets. The relative weights of the lung were affected (p < 0.05) by dietary supplementation. Serum cholesterol concentration reduces (p < 0.05) with increased dietary MLM supplementation levels from 1.0% to 1.5%. Superoxide dismutase and glutathione peroxidase levels increased (p < 0.05) in the broiler chickens fed a 1.5% MLM supplemented diet, compared to those fed the control and other diets. Meat cholesterol of the chickens fed 1.0%, and 1.5% MLM supplemented diets were lower (p < 0.05) than the experimental birds fed the rest diets. In conclusion, the 1.5 % MLM dietary supplementation improves body weight gain, reduces the serum cholesterol concentration, increases the serum superoxide dismutase and glutathione peroxidase activities of the chickens and reduced the meat cholesterol.